Splenic vein aneurysm with calcification of splenic and portal veins - Kocakoc, E; Kiris, A; Bozgeyik, Z; Uysal, H; Artas, H (John Wiley & Sons Inc, 2005)
Splenic vein aneurysm is a rare disease, and calcifications in the portal venous system are also rare. Here! we present a case of splenic vein aneurysm associated with calcification of the splenic and portal veins, a condition that to our knowledge has not been reported before. (C) 2005 Wiley Periodicals, Inc.
Keywords: splenic vein; aneurysm; portal vein; calcification; magnetic resonance; ultrasonography